Impact of hot electrons on optical excitation of terahertz radiation by beating of supergaussian lasers in electron-positron collisional plasma. (27th October 2020) - Divya, S
Abstract: The mechanism of generation of terahertz (THz) radiation with beating of two supergausssian lasers in corrugated density plasma containing hot electron-positron (e-p) is revisited. Resonance condition for optical excitation of THz emission is reported to be modified due to finite temperature of plasma species (electrons-positrons to the few order keV range) in the presence of weak collisions. The collision frequency is optimized to the range ν ≤ 0.5 ω p in the e-p plasma depending on the temperature and collisional rates. The effect of electron temperature, collision frequency and suitability of supergaussian laser is investigated on phase modulation to achieve highest emitted THz field with 6% efficiency of the mechanism.